Quantity and Quality of Sleep among Medical and Paramedical Students: A Comprehensive Study and Analysis - Wani, Pinaki (International Journal of Innovative Research in Medical Science, 2024)
Introduction: Sleep plays a crucial role in maintaining cognitive function and overall well-being, particularly among medical and paramedical students who face unique stressors impacting their sleep patterns and academic performance. Understanding the sleep quality of these students is essential for addressing potential issues and promoting their overall health and academic success. Aim: This study aimed to comprehensively evaluate the sleep quality of undergraduate medical and physiotherapy students from an urban tertiary health care center using the Pittsburgh Sleep Quality Index (PSQI). Methodology: A total of 294 students participated in the study, including 226 MBBS and 68 Physiotherapy students, all of whom were females. The PSQI was utilized to assess various components of sleep quality among the participants. Data analysis involved examining sleep latency, duration, efficiency, disturbances, daytime dysfunction, and overall sleep quality. Comparative studies worldwide were also referenced to contextualize the findings. Results: The study revealed that 31.3% of participants experienced poor sleep quality, with 34.51% of MBBS and 21% of Physiotherapy students exhibiting significant sleep disturbances. Gender-wise, 30 male MBBS students, 48 female MBBS students, and 14 female physiotherapy students experienced poor sleep quality. Analysis of PSQI components highlighted varying sleep patterns among students, emphasizing challenges such as sleep latency, duration, efficiency, disturbances, and daytime dysfunction. Comparative studies conducted worldwide supported the high prevalence rates of poor sleep quality among medical students. Contributing factors identified included academic stress, disrupted learning styles, and increased exam pressures. Conclusion: The findings underscore the critical need for interventions to address sleep quality issues among medical and paramedical students, with the goal of enhancing their well-being and academic performance. Further research is recommended to explore additional factors influencing sleep quality in this demographic, paving the way for more targeted interventions and support systems. Recognizing the significance of sleep quality in student populations is paramount for fostering their holistic development and success in academic pursuits.